ANALISIS STRATEGI SHOPEE SEBAGAI SALAH SATU MARKETPLACE TERBESAR - Muhammad Fikra Ilyasa; Humaira Dhiya Wijayanti; Agnia Melani; Renata Aura Faatihah; Rahmadanti Atha Yumna (Taksasila Edukasi Insani, 2026)
In the era of online shopping, increasing internet usage has significantly influenced the development of the e-commerce industry in Indonesia. This study aims to determine the impact of e-commerce, particularly on the Shopee marketplace, the most popular buying and selling platform in Indonesia. The method used was a literature review, reviewing the results and opinions of several previous studies as a theoretical basis.The results indicate that Shopee has successfully become a major leader in the Indonesian e-commerce market. With the right strategy, Shopee has been able to build an image as the largest and most popular marketplace. Shopee focuses on customer satisfaction by providing quality products, secure transactions, and affordable prices. Shopee's success is not only due to public interest in online shopping but also to the company's efforts to provide the best shopping experience for its users.Kata Kunci: E-commerce, Shopee, Online Buying and Selling, Marketplace